Family planning preferences in transgender youth in an urban multi-disciplinary gender clinic - Ryan Conard; Lisal Folsom (Journal of Clinical & Translational Endocrinology, 2024)
Background: Known barriers to family planning in the transgender population include low utilization of cryopreservation and decisional regret. There is growing data on the risk of infertility with GAHT, and on to what degree transgender adolescents feel informed about fertility and family planning options. Objective: Assess preferences regarding options for family planning and fertility preservation in transgender adolescents treated with GAHT in a pediatric endocrinology gender clinic. The goal is to enhance patient education about potential effects of GAHT on fertility and options for family planning. Methods: Forty one adolescents aged 10 years and older treated with GAHT in an urban outpatient pediatric endocrinology clinic were surveyed over a 6-month period from January to June 2022. Survey questions were multiple choice, Likert scale, and open-ended. Participants were at least 10 years of age, actively followed in the clinic, and receiving GAHT at time of enrollment. Results: Forty one participants completed the survey. Four (10 %) expressed interest in discussing family planning with their provider. Eighteen (45 %) were open to discussion in the future; 16 (39 %) were not interested at all. 12 (30 %) participants were planning for future parenthood, and 16 (40 %) participants were undecided. Of those interested in parenthood 7 (53.8 %) planned to adopt or foster. Barriers to family planning expressed included financial concerns, potential need to pause GAHT, and social stigma of transgender parenthood. Twenty (50 %) participants recalled prior family planning discussion with their endocrinologist. Conclusion: Family planning discussions may not be optimally impactful given that 50 % of participants did not recall the conversations. Family planning is a lower priority in this population as most desired to postpone discussion with their provider despite choosing treatment that could influence fertility. It is essential to identify methods to engage transgender youth in discussions related to family planning during GAHT.